Results of Surveillance of Influenza in Out-patients Influenza-like Illness (ILI), Inpatients Severe Acute Respiratory Illness (SARI) and Severe Pneumonia cases in Community Based Medical College Hospital, Bangladesh, Mymensingh during the period of May 2 (Community Based Medical Journal, 2015)
Influenza is prevalent in Bangladesh among both adults and children. This observation is proved by recent population-based estimates. A hospital based surveillance study was conducted under the supervision of ICDDRB at Community Based Medical College Hospital, Bangladesh (CBMCH,B). To explore the epidemiology and seasonality of influenza throughout the Mymensingh region and all age groups, we analyzed the data collected during the period of May 2007 to May 2012 for a period of 5 years. The result revealed that out of 1014 patients, 140(14%) were influenza positive by real time RT-PCR. Among the sample-positive patients, 90(64%) were type A and 50(36%) type B. Hemagglutinin subtyping of type A virus detected 7(8%) A/H1 and 42(47%) A/H3, 41(46%) H1N1 pdm09 but no A/H5 or other novel influenza strains. The frequency of influenza cases was highest among children aged under 5 year 44%, while the laboratory confirmed cases were highest among patients aged under 1 year to 30 years 54%. We identified a distinct influenza peak during the rainy season (May to September), highest in July and August. There is a very low presence of influenza in the month of October, November and December (2, 1, 2 flu positive cases in 5 year period respectively). Our surveillance data confirms that influenza is prevalent throughout Mymensingh, affecting a wide range of ages and causing considerable morbidity and hospital care. A unimodal influenza seasonality may allow Mymensingh, Bangladesh to time annual influenza prevention messages and vaccination campaigns to reduce the national influenza burden. To scale-up such national interventions, we need to quantify the national rates of influenza and the economic burden associated this disease through further studies.CBMJ 2015 January: Vol. 04 No. 01 P: 03-12